Doing good and doing well, navigating hybrids’ tensions: the case study of “Risana Outpatient Clinic” purpose-driven enterprise - Ceraulo, Simona (Piccola Impresa / Small Business, 2023)
Purpose. The aim of this study is to explore if and to what extent Humanistic Management (HM) values can help hybrid/purpose driven businesses to successfully handle tensions among different institutional logics, allowing them to fulfill both their economic and social goals. Design/methodology/approach. The following research questions “How does a purpose-driven enterprise explicitly inspired by HM principles manage the tensions between the economic rationale and its social mission? Is it effective?” have been investigated through a qualitative approach. The case study examines a cooperative adhering to the Economy of Communion (EoC) network, which can be considered expressive of a HM approach. Tensions were observed during the Pandemic and analyzed through a stakeholder framework. Findings. The body of values, such as solidarity, reciprocity, gratuitousness, dialogue, trust, rooted in the organizational culture, played a central role in guiding the company to make winning strategic decisions. A new hybrid “communion” logic was observed, embracing both commercial and social logics, overcoming logic conflicts, coping with the Covid-19 challenges and allowing the company to reach its economic and social goals. Practical and Social implications. This study provides empirical evidence of the effectiveness of an HM approach to managing tensions between institutional logics in a hybrid organization, through a clear focus on the corporate purpose and the promotion of an inclusive, participatory and cooperative relational culture. Originality of the study. This paper highlights the strategic relevance of purpose and an organizational culture inspired by the HM / EoC values in managing tensions between institutional logics through an empirical approach.